Exploring the biosurfactant potential of Actinobacteria isolated from Ruta graveolens - Ferreira , Sílvia; Ribeiro , Inês; Oliveira , Rui S.; Carvalho , Maria de Fátima (Scientific Letters, 2024)
Background: Biosurfactants are surface-active compounds known for their emulsifying properties and numerous advantages, including low environmental toxicity, eco-friendliness, biodegradability and acceptability. These molecules are amphiphilic, containing both hydrophilic and hydrophobic ends, allowing them to interact at the aqueous-non-aqueous interface [1]. Bacterial biosurfactants are interesting due to their various fields of applications, including biomedicine, cosmetics, food, pharmaceutics, water treatment and oil recovery [2]. Actinobacteria are an important group of microorganisms with high potential for producing different bioactive metabolites including antimicrobial, anticancer and other pharmaceutical compounds [3]. Medicinal plants, such as Ruta graveolens, are a rich source of bioactive compounds, and the association of actinobacteria endophytes with such plants are an attractive source for bioprospecting for novel compounds with biomedical and industrial applications [3]. Objective: The purpose of this study was to explore the biosurfactant activity of actinobacterial strains previously isolated from R. graveolens. Methods: Fifteen previously isolated actinobacterial strains were inoculated into 100 mL Erlenmeyer flasks containing 30 mL of Kim’s broth supplemented with 3% filtered olive oil as a hydrophobic carbon source. After two weeks, biosurfactant production was analyzed by measuring the emulsification activity. Results: Eight out of the 15 actinobacterial strains showed emulsification activity. All results were compared with a positive control consisting of Triton X100 (1mg/ml), and a negative control consisting in Kim’s broth. Almost all strains that revealed positive activity are affiliated to the actinobacterial species Tsukamurella tyrosinosolvens (7/8), with one strain belonging to the species Microbacterium gisengiterae. Comparative analysis with the positive control (with an emulsification activity of 60%), indicated that 3/8 samples showed high emulsification activity (>40%), 1 showed moderate activity (37%) and 4/8 showed low/moderate activity (20-30%). Conclusions: The subsequent phases of this study will involve analyzing if the potential biosurfactant compounds can reduce the surface tension and if they can represent new molecules.